Association of abuse-specific, familial, and post-incident factors with patterns of behavior problems in sexually abused preschoolers. (August 2020) - Choi, Ji Young
Highlights: We identified data-driven subtypes of behavior problems of sexually abused preschoolers and investigate factors differentiating the subtypes. Four classes were obtained from the LPA: Mild, Moderate, High Internalizing groups, and High Internalizing and Externalizing group. Victimization by acquaintances increased the likelihood of developing a higher internalizing problem profile. Marital conflict was a significant predictor for distinguishing the High Internalizing/Externalizing group from other groups. It may be useful to explore whether marital conflict interferes with adequate soothing or parenting for sexually abused preschoolers. Abstract: Background: The negative effects of child sexual abuse are well known; however, limited research has been conducted on the symptom patterns and their predictors in sexually abused preschoolers. Objective: The aim was to identify the subtypes of parent-reported behavior problems and sexual behaviors among sexually abused preschool-aged children using latent profile analysis (LPA) and investigate factors that can affect the identified subtypes. Participants and Setting: Participants included 194 (28 males; 166 females) sexually abused children (age, 3–6 years) located in the Republic of Korea. Methods: LPA was performed using the seven syndrome scales of the Korean version of the Child Behavior Checklist for ages 1.5–5 and the Child Sexual Behavior Inventory as indicators. Demographic, sexual abuse characteristics, familial variables, and post-incident variables were compared between the derived classes. Multinomial regression analysis was performed to investigate the predictors for each class. Results: Four classes were obtained from LPA: "Mild" (29.9 %), "Moderate" (18.0 %), "High Internalizing" (21.6 %), and "High Internalizing/Externalizing" (29.9 %). The Mild group included more cases of a single episode of abuse or victimization by strangers and immediate disclosure. Marital conflict was significant in differentiating the High Internalizing/Externalizing group from the other groups. Conclusions: Sexually abused preschoolers could be classified into three groups according to severity, and the severe group could be classified into two heterogeneous groups. Furthermore, relationship with the perpetrator may predict more serious internalizing behavior problems, and marital conflict may be associated with complex symptoms involving externalizing and sexual behavior problems.